Women Brazilian Jiu-jitsu practitioners showed a higher incidence of concussion: an epidemiological analysis - Carvalho,Gustavo Nascimento de (2022)
Abstract Knowledge about the prevalence of concussion in combat sports is important information to keep athletes’ and practitioners’ physical integrity in different modalities such as Brazilian jiu-jitsu (BJJ). Therefore, this study aimed to compare concussions incidence in BJJ between men and women practitioners. A randomized sample of 779 (689 men and 90 women) BJJ practitioners (age: 32.4± 9.8 years, training-time: 57.3± 54.4 months, training frequency: 3.4± 1.3 times/week). The injury analysis was done using a questionnaire with demographic data and a survey about concussions. The main results showed that women had a significantly higher frequency of concussions in training than men [38 (41%) women vs 147 men (20,5%); p ≤ 0.001]. Furthermore, women had a significantly higher frequency of loss of consciousness than men [13 (8.8%) men vs 4 (11%) women; p = 0.009], among the symptoms resulting from a concussion, headache, dizziness, and loss of balance, represented the most common symptoms in those affected by concussion, regardless of gender. The results of this study may be helpful to athletes, coaches, and federations to prevent this type of injury, mainly in women.